Use of the blog for the development of a higher basic mathematics didactic unit (8th grade) - Carmen Narcisa Franco Zambrano, Marcos Alejandro Yánez Rodríguez (International Journal of Advanced Science and Technology, 2020)
The purpose of the research is to present the use of the blog as a didactic-technological resource, to develop a Higher Basic Mathematics unit (8th grade), in order for students to achieve meaningful learning, taking into account the importance of incorporating Information and Communication Technologies in the teaching-learning process, thus giving a different pedagogical horizon, since in general there are discontents in the understanding of concepts; In addition, the subject is usually seen as abstract and impractical in everyday life. A descriptive research was carried out with a qualitative approach, achieving that through this proposal a strategy is shown that facilitates the academic and innovative work of the teacher to offer a viable response to the students, presenting the subject from a more practical and real perspective, given the facilities offered by web 2.0 resources.